Solving Bigeometric Volterra Integral Equations by Using Successive Approximations Method - Nihan Güngör (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, the successive approximations method has been applied to investigate the solution for the linear bigeometric Volterra integral equations of the second kind in the sense of bigeometric calculus. The conditions to be taken into consideration for the bigeometric continuity and the uniqueness of the solution of linear bigeometric Volterra integral equations of the second kind are researched. Finally, some numerical examples are presented to illustrate successive approximations method.